2013
DOI: 10.1038/nm.3362
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with interferon-α2b and ribavirin improves outcome in MERS-CoV–infected rhesus macaques

Abstract: The emergence of Middle East respiratory syndrome coronavirus (MERS-CoV) is of global concern – causing severe respiratory illness with 97 confirmed cases and 46 deaths1. Therapeutic interventions have not been evaluated in vivo, thus patient management relies exclusively on supportive care, which given the high case-fatality rate is not highly effective. The rhesus macaque is the only known disease model for MERS-CoV, developing an acute localized-to-widespread pneumonia with transient clinical disease2,3 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
418
2
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(442 citation statements)
references
References 32 publications
8
418
2
14
Order By: Relevance
“…In vitro activity of interferon was further enhanced by the addition of ribavirin [30]. Recently, animal studies utilizing Rhesus Macaque monkeys infected with MERS-CoV were published [31][32][33]. Using intratracheal, ocular, oral and intranasal inoculation of MERS-CoV, Rhesus macaques developed a transient lower respiratory tract infection and had histopathologic changes of the disease and developed neutralizing antibodies [33].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro activity of interferon was further enhanced by the addition of ribavirin [30]. Recently, animal studies utilizing Rhesus Macaque monkeys infected with MERS-CoV were published [31][32][33]. Using intratracheal, ocular, oral and intranasal inoculation of MERS-CoV, Rhesus macaques developed a transient lower respiratory tract infection and had histopathologic changes of the disease and developed neutralizing antibodies [33].…”
mentioning
confidence: 99%
“…From these studies, the pathogenesis of the disease revealed that MERS-CoV results in clinical disease, promotes virus shedding and replication in respiratory tissues, and that cytokines and chemokines peaked early in infection and decreased over time [33]. An earlier rhesus macaque model of MERS-CoV infection showed that both IFN-a2b and ribavirin combinations was effective in limiting MERS-CoV disease, clinically and radiographically [31]. In a recent observational study of five MERS-CoV patients treated with a combination of interferon and ribavirin, the median time from admission to therapy was 19 (range 10-22) days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their practical use in humans is challenging because, if not infected while in a healthcare setting, humans usually present for care with well advanced disease. [107,108] Combined treatments which reduce viral replication and the host immune response to it are likely to be valuable developments. [15] A wide range of repurposed or novel potential antivirals including polymerase, nucleotide synthesis and protease inhibitors and fusion-inhibiting peptides [64,87,[109][110][111][112][113] have been investigated.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Tip 1 interferonların insan akciğer doku kültürlerinde MERS-CoV replikasyonunu inhibe ettiği göste-rilmiştir. Yine yapılan bir çalışmada ribavirin ve interferon-alfa 2b'nin Vero and LLC-MK2 hücre kültürlerinde replikasyonu azalttığı gösterilmiş-tir (24)(25)(26).…”
Section: Tedavi̇unclassified